2021
DOI: 10.3390/jpm11060500
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Role of miRNA in Environmental Exposure to Plasticizers: A Systematic Review

Abstract: The daily environmental exposure of humans to plasticizers may adversely affect human health, representing a global issue. The altered expression of microRNAs (miRNAs) plays an important pathogenic role in exposure to plasticizers. This systematic review summarizes recent findings showing the modified expression of miRNAs in cancer due to exposure to plasticizers. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, we performed a systematic review of the liter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The results of this study indicated significant positive correlations between urinary MEHP and the expression of miR-155 and miR-208a. Ferrante et al 52 stated that the plasticizers' interaction with several miRNAs might cause significant changes in miRNA-mediated regulation and functions. This study implied that the upregulation of miR-155 and miR-208a expression may mediate the association between phthalate exposure and CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicated significant positive correlations between urinary MEHP and the expression of miR-155 and miR-208a. Ferrante et al 52 stated that the plasticizers' interaction with several miRNAs might cause significant changes in miRNA-mediated regulation and functions. This study implied that the upregulation of miR-155 and miR-208a expression may mediate the association between phthalate exposure and CHD.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a recent revision indicates that plasticizers alter the expression of different miRNAs. Such a genotoxic/oncogenic response could eventually lead to alterations in the cell signaling pathways involved in different overlapping cellular processes [43]. As a consequence, they can be useful targets in the assessment of the harmful effects of environmental agents, including nanomaterials.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the results presented herein provide more evidence that the analyses of epigenetic components may be used to face public health issues related with cancer prevention [ 27 ], with particular reference to the identification of the environmental risk factors to be prevented.…”
Section: Discussionmentioning
confidence: 99%